Ventricular high-rate episodes predict increased mortality in heart failure patients treated with cardiac resynchronization therapy. (February 2015) - Jacobsson, Jonatan; Reitan, Christian; Platonov, Pyotr G.; Borgquist, Rasmus
Abstract Objectives. Cardiac Resynchronization Therapy (CRT) for heart-failure patients has a well-documented positive effect, but the overall mortality in this group remains high. This study aimed to explore whether additional information from the device post-implant (occurrence of ventricular high-rate episodes), could add prognostic value for patients on CRT-pacemaker (CRT-P) treatment. Design. Clinical data and device-interrogation data were retrospectively gathered from the medical records of 220 patients treated with CRT-P. Ventricular high-rate (VHR) episodes were defined as a ventricular rate ≥ 180 beats per minute. The primary outcome was 5-year mortality. Results. During follow-up, 132 patients (60%) died or underwent heart transplant. Overall, the 5-year mortality rate was 52%; 77% for patients with VHR during the first year of follow-up and 48% for patients without VHR during the first year of follow-up (p = 0.001). In a multivariate model, the occurrence of VHR episodes was an independent predictor of 5-year mortality (HR 9.96, p = 0.022). The most common cause of death was heart failure, and death from arrhythmia did not differ between groups (p = 0.065). Conclusions. In heart-failure patients with CRT-P therapy, occurrence of VHR episodes within the first year post-implant was an independent predictor of higher 5-year mortality and inferior long-term survival, but not of death from malignant arrhythmia.